2010
DOI: 10.1111/j.1365-2133.2010.09911.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel fibrotic disorder associated with increased dermal fibroblast proliferation and downregulation of genes of the microfibrillar network

Abstract: Clinical evaluation of a young woman with subcutaneous fibrotic nodules, progressive distal joint contractures and marfanoid stature revealed a previously unrecognized fibrotic disorder characterized by several unique phenotypic features and some features overlapping with known disorders. Mutational analysis of the FBN1 and FBN2 genes excluded Marfan syndrome and congenital contractural arachnodactyly. MMP2 gene sequence analysis excluded multicentric osteolysis, nodulosis and arthropathy. The lack of mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…19, 20, 21 Expression changes in microfibrillar proteins such as MFAP5, is known to participate in collagen synthesis and accumulation. 22 Lemaire et al 23 have demonstrated that MFAP5 could enhance type I collagen matrix by stabilizing type I procollagen. Furthermore, it has been shown that MAGP-1, which is structurally related molecule to MFAP5, could bind to type VI collagen.…”
Section: Discussionmentioning
confidence: 99%
“…19, 20, 21 Expression changes in microfibrillar proteins such as MFAP5, is known to participate in collagen synthesis and accumulation. 22 Lemaire et al 23 have demonstrated that MFAP5 could enhance type I collagen matrix by stabilizing type I procollagen. Furthermore, it has been shown that MAGP-1, which is structurally related molecule to MFAP5, could bind to type VI collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells, LOXL1 synthesis and processing were evaluated by Western blot analysis using LOXL1 polyclonal rabbit primary antibody (Zymed Laboratories, San Francisco), and polyclonal anti-BMP-1 antibody (Affinity Bioreagents). LOXL1 catalytic activity assays were performed in media fractions of cells cultured for 48 hours in phenol red and serum free media using the Amplex Red assay (Life Technologies) as previously described 9 . LOXL1 sub-cellular and ECM localizations were determined in fluorescent immuno-cytochemistryexperiments.…”
Section: Methodsmentioning
confidence: 99%
“…It has been involved in different fibrotic disorders and its expression, regulation and activity can play an important role in the initial steps of fibrosis 6. An imbalance in MMP expression pattern, including a downregulation in MMP2, was demonstrated in the fibroblasts of a patient with subcutaneous fibrotic nodules, severe progressive distal joint contractions and marfanoid stature 7. It leads to a disorderly ECM deposition and to a TGF-beta-independent dermal fibrosis.…”
mentioning
confidence: 99%